Is marketing digitization important? - Suasana, I Gst. A. Kt. Gd; Warmika, I Gde Ketut; Ekawati, Ni Wayan; Rastini, Ni Made (International journal of data and network science (Print), 2022)
Small industries tend to achieve marketing performance harder than their bigger counterparts, constrained by limited resources when compared to large businesses, especially during the Covid-19 pandemic. These constraints seem to still be relatively difficult to find a way out and result in low marketing performance including small industries in Denpasar. The purpose of the study is to explain the influence of entrepreneurial personality on marketing performance and to investigate the role of digitalization of marketing as a moderation of the influence of entrepreneurial personality on the marketing performance of small industries in Denpasar. The subject of the study was a small industry in Denpasar, represented by the owner / manager as a source. The sample size was set at 150 respondents. Analysis techniques use Moderated Regression Analysis (MRA). The results found that entrepreneurial personality has a significant influence on marketing performance, and digitalization of marketing acts as a quasi-moderation of the influence of entrepreneurial personality on the marketing performance. Small industries should be more active in exploring paid online media since it has a wider reach, such as existing market places or utilizing government-provided facilities, be careful about setting production targets and setting targets for special forces on marketing performance.